Electromagnetic Wave Reduction Of Multiwalled Carbon Nanotubes (mwcnt) Mixed Nanometer Cofe2o4 At Higher Frequency Range - F.M. Idris; H. Kaco; S.M. Mohd; N.M. Jan; F. Esa; Z.M. Idris (Elsevier, 2024)
Indexed by SCOPUS/ERA